SPE European Formation Damage Conference 2005
DOI: 10.2118/95021-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Simulator For Produced Water Reinjection in Thermally Fractured Wells

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe objective of the analytical simulator presented here is to predict the opposite and complex effects induced by the injected produced water temperature and formation damage on thermally fractured wells. The deposition of solid particles and oil droplets in a fracture and its effect on the Injectivity Index evolution of an injector is then simulated. The principle is to inject cooled waters like sea water for example during a certain period of time to enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…With PWRI, sustaining a long-term injection rate is likely to require fracturing (Zhang et al 1993;Detienne et al 2005; Van den Hoek et al 2008). Matrix injection results in a continuous well-injectivity decline even in soft formations (Detienne et al 2005;Abou-Sayed et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With PWRI, sustaining a long-term injection rate is likely to require fracturing (Zhang et al 1993;Detienne et al 2005; Van den Hoek et al 2008). Matrix injection results in a continuous well-injectivity decline even in soft formations (Detienne et al 2005;Abou-Sayed et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Matrix injection results in a continuous well-injectivity decline even in soft formations (Detienne et al 2005;Abou-Sayed et al 2007). Actually, recent field evidence indicates that most water-injection wells are likely to be fractured (Abou-Sayed et al 2005;Abou-Sayed et al 2007; Van den Hoek et al 2008) and that regular well acidizing is required to maintain injectivity even with clean water (Van den Hoek et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fracturing of seawater injection wells has proven to give sustained high rates over long life, with fracture growth assisted by cold injection temperatures, typically referred to as thermal fracturing 3,4 . However, studies 5,6 have suggested that produced water injectors are more prone to fracture damage and warmer injection means they do not achieve as much benefit from thermal fracturing. Attempts have been made on ETAP, with limited success, to improve PWRI injection rates using short term seawater injection.…”
Section: Experience From Pwri-1 and Pwri-2mentioning
confidence: 99%
“…A new method was recently proposed 6 to quantify parameters λ and β from laboratory pressure measurements using the called 3 point pressure method. Other models 7,8 dedicated to simulate produced water re-injection under fracturing conditions, the depth of the internal damage is simply calculated from the injected volume of oil assuming an oil saturation and a fixed damaged permeability in the invaded zone. For other works 9 the concept of Barkman and Davidson is still used to simulate produced water injectivity decline.…”
Section: Introductionmentioning
confidence: 99%